OP17 Do Low Levels of Psychological Distress Predict Mortality? Evidence from an Individual Participant Meta-Analysis of ten Prospective Cohort Studies. (17th September 2012) - Russ, TC; Stamatakis, E; Hamer, M; Starr, JM; Kivimaki, M; Batty, GD
Abstract : Background: A series of studies have linked psychological distress (depression and anxiety) with cause-specific mortality, but the risk of lower, sub-clinically symptomatic, levels of distress – hitherto of little interest to specialist mental health practitioners – has not been quantified. Methods: We conducted an individual participant meta-analysis of ten large prospective cohort studies from the Health Survey for England. Baseline psychological distress was measured using the 12-item General Health Questionnaire, and mortality from death certification. The analytical sample comprised 68, 222 individuals from general population samples of adults aged 35 and over, free of cardiovascular disease and cancer and living in private households in England at study baseline. The main outcome measures were death from all causes (n=8, 365), cardiovascular disease (n=3, 382), all cancers (n=2, 552), and external causes (n=386). Mean (standard deviation) follow-up was 8.2 (3.5) years. Results: There was a positive, dose-response association between psychological distress across the full range of severity and mortality risk (age- and sex-adjusted hazard ratio for General Health Questionnaire scores of 1–3 compared to zero: 1.20, 95% CI 1.13 to 1.27; scores 4–6: 1.43 1.31 to 1.56; and scores 7–12: 1.94, 1.66 to 2.26; p for trend <0.001). This association remained after adjustment for somatic co-morbidity plus behavioural and socioeconomic factors. A similar association was found for death from cardiovascular disease, cancer, and external causes. Conclusion: Psychological distress is associated with increased risk of mortality from several major causes in a dose-response pattern. Even at lower levels of distress the mortality risk was elevated.